Eksistensi Container House sebagai Objek Jaminan Berdasarkan Hukum Jaminan di Indonesia - Darda Davita, Diva (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Container house is a building made of used containers hich is a movable object that can be modified into a house or residential place that is an immovable object. Therefore, if the owner of the Container house ants to collateralize the container it ill cause a gap between positive law and social facts related to hat collateral law ill be charged against the Container house. so the purpose of this study is to analyze the status of the container house in the perspective of existing laws in Indonesia and in the status of the container can the container house be used as a collateral object. The method used in this research is normative research method. The result of the research is that first, a container house is a movable object ith the characteristics of a physical building made from containers that does not require construction ork so it does not require a construction permit, can be transferred and has economic value. However, normatively, there are no laws and regulations governing it so that its ownership has no guarantee of legal certainty. Second, container houses can be charged ith fiduciary guarantees, so the execution of container houses is carried out in accordance ith Article 15 paragraph (2) of the UUJF if there is consent from the fiduciary. However, if the fiduciary grantor does not agree to surrender the object of the fiduciary guarantee, then the execution is carried out based on the Constitutional Court Decision Number 18/PUU/XVII/2019, namely through a court order.